2002
DOI: 10.1080/13607860220126835
|View full text |Cite
|
Sign up to set email alerts
|

Minority ethnic groups in dementia care: A review of service needs, service provision and models of good practice

Abstract: Sixty-seven English language articles were obtained for the review, the majority of which (44, 65.7%) had US origins. Broadly, the main issues covered in the literature were the under-utilization of services by minority ethnic groups; the prevalence of dementia in different ethnic groups; the experience of care giving in different racial groups and language as a factor in cognitive assessment. Although it has been argued that the instruments used to assess cognitive function are culturally biased, the availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 34 publications
3
78
0
Order By: Relevance
“…Similarly, training staff in cultural awareness and sensitivity and conducting language-appropriate cognitive testing may help address some disparities (Daker-White et al, 2002).…”
Section: Cultural Competencementioning
confidence: 99%
“…Similarly, training staff in cultural awareness and sensitivity and conducting language-appropriate cognitive testing may help address some disparities (Daker-White et al, 2002).…”
Section: Cultural Competencementioning
confidence: 99%
“…36 Earlier research identified the importance of incorporating cultural values in dementia assessment and treatment protocols. 37,38 As a first step, researchers partnered with members of an Aboriginal Grandmothers group with experience in providing care to Aboriginal seniors. The group's coordinator at the community clinic attended some meetings and traveled with the researchers on northern visits.…”
Section: Development Of Culturally Appropriate Cognitive Assessment Mmentioning
confidence: 99%
“…Patients from ethnic minorities often present symptoms in a different way than other patients [3], and valid tools for cross-cultural cognitive assessment are currently lacking in Europe [2], which may have contributed to the poor documentation of a history of progressive cognitive decline that was supported by cognitive test results. Based on previous studies that report significant challenges in cross-cultural cognitive assessment [2,4,21], we had a particular interest in the methods applied for cognitive testing. After a more in-depth evaluation of the methods applied for cognitive testing, we found that satisfactory cognitive testing was performed in no more than one third of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although symptoms of dementia are similar across races and ethnicities, dementia may be difficult to diagnose in elderly patients from ethnic minorities. The patients often have limited linguistic abilities in the dominant language [1,2], they often present their dementia symptoms in a different way than other patients [3], and cross-culturally validated cognitive instruments and rating scales are lacking [2,4]. Moreover, there is a stigma and taboo attached to mental health problems in some ethnic minorities [5], which may affect the awareness and communication of problems.…”
Section: Introductionmentioning
confidence: 99%